2014
DOI: 10.1097/qai.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

The VACS Index Predicts Mortality in a Young, Healthy HIV Population Starting Highly Active Antiretroviral Therapy

Abstract: Background The Veterans Aging Cohort Study (VACS) Index is a weighted combination of age and eight clinical variables. It has been well correlated with all-cause mortality among HIV-infected patients. The U.S. Military HIV Natural History Study (NHS) cohort provides a different validation population profile, being younger and healthier. A significant portion of the US HIV population is similarly composed, so evaluation of the VACS Index in this population is of great interest. Methods NHS subjects have medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…We also relied on ICD-9-CM data for defining co-morbidities, as a number of validation studies support the use of diagnostic codes for this purpose. 3, 22, 23, 29 For ICD-9-CM codes related to chronic pain, we found that HIV-infected patients were less likely to receive a chronic pain diagnosis; we postulate that these findings may reflect differences in coding practices between Infectious Disease vs. General Medicine providers, in particular differences in their approach to pain management, with Infectious Disease providers more likely to code for infectious or medical comorbidities. 13 Finally, our use of two OT guidelines, both of which were published and subsequently updated during the period of observation, would appear to present a challenge to assessing guideline-concordant care.…”
Section: Discussionmentioning
confidence: 81%
“…We also relied on ICD-9-CM data for defining co-morbidities, as a number of validation studies support the use of diagnostic codes for this purpose. 3, 22, 23, 29 For ICD-9-CM codes related to chronic pain, we found that HIV-infected patients were less likely to receive a chronic pain diagnosis; we postulate that these findings may reflect differences in coding practices between Infectious Disease vs. General Medicine providers, in particular differences in their approach to pain management, with Infectious Disease providers more likely to code for infectious or medical comorbidities. 13 Finally, our use of two OT guidelines, both of which were published and subsequently updated during the period of observation, would appear to present a challenge to assessing guideline-concordant care.…”
Section: Discussionmentioning
confidence: 81%
“…Although risk stratification tools have been developed to predict HIV disease progression and prognosis, [24][25][26] a similar tool to aid in the identification of patients likely to miss appointments is not available. Beginning in July 2013, clinicians at the Vanderbilt Comprehensive Care Clinic (VCCC, Nashville, TN) implemented an evidence-based tool for assessing the risk of virologic failure at 1 year 27 among patients with uncontrolled viremia-defined as HIV-1 viral load (VL) > 200 copies/milliliter (mL).…”
Section: Aids Patient Care and Stdsmentioning
confidence: 99%
“…As a measure of overall severity of illness, we used the VACS Index, which incorporates age, HIV-1 RNA viral load, CD4 count, hemoglobin, FIB-4, estimated glomerular filtration rate, and hepatitis C virus. The VACS Index is a validated prognostic measure, 28,29,[37][38][39][40] which is predictive of morbidity and mortality in both HIVinfected and uninfected patients (in calculating the index, the assumption is made that uninfected patients have a CD4 count > 500 cells/μL and viral load < 20 copies/ml). 29,41 Higher scores are indicative of higher all-cause mortality risk.…”
Section: Covariatesmentioning
confidence: 99%